2022
DOI: 10.1038/s41467-021-27610-z
|View full text |Cite
|
Sign up to set email alerts
|

A bispecific monomeric nanobody induces spike trimer dimers and neutralizes SARS-CoV-2 in vivo

Abstract: Antibodies binding to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike have therapeutic promise, but emerging variants show the potential for virus escape. This emphasizes the need for therapeutic molecules with distinct and novel neutralization mechanisms. Here we describe the isolation of a nanobody that interacts simultaneously with two RBDs from different spike trimers of SARS-CoV-2, rapidly inducing the formation of spike trimer–dimers leading to the loss of their ability to attach t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 61 publications
3
59
0
1
Order By: Relevance
“…All-atom MD simulations totaling 27.6 µs in length using the recently solved structures of the RBD of SARS-CoV-2 S protein in complex with nanobodies H11-H4 [145], H11-D4, and Ty1 revealed interactions between RBD and the nanobodies and estimated that the binding strength of the nanobodies to RBD is similar to that of ACE2 [145]. Together, our MD simulations suggest that H11-H4 and Ty1 abrogate ACE2 binding via different mechanisms, whereas H11-D4 is the least effective inhibitor among the three examined nanobodies, which is consistent with the experimental studies showing the lowest K D value for Ty1 and the highest for H11-D4 nanobody [89,95].…”
Section: Computational Studies Of Sars-cov-2 S Protein Binding Mechan...supporting
confidence: 88%
See 4 more Smart Citations
“…All-atom MD simulations totaling 27.6 µs in length using the recently solved structures of the RBD of SARS-CoV-2 S protein in complex with nanobodies H11-H4 [145], H11-D4, and Ty1 revealed interactions between RBD and the nanobodies and estimated that the binding strength of the nanobodies to RBD is similar to that of ACE2 [145]. Together, our MD simulations suggest that H11-H4 and Ty1 abrogate ACE2 binding via different mechanisms, whereas H11-D4 is the least effective inhibitor among the three examined nanobodies, which is consistent with the experimental studies showing the lowest K D value for Ty1 and the highest for H11-D4 nanobody [89,95].…”
Section: Computational Studies Of Sars-cov-2 S Protein Binding Mechan...supporting
confidence: 88%
“…Many other recent studies have demonstrated and confirmed the potential of linker-based bi-paratopic or multi-paratopic nanobodies for enhanced blocking and neutralization of SARS-CoV-2 variants. The avidity effect was also observed by Hanke and colleagues that presented a bispecific monomeric nanobody that can promote the formation of the S trimer dimers and neutralizes SARS-CoV-2 in vivo [ 95 ]. This study demonstrated that multimerization of nanobodies can substantially improve virus neutralization potency, and the cryo-EM structure of the Fu2-spike complex with S protein revealed a remarkable head-to-head dimerization of the trimeric spike, bound by six molecules of Fu2 [ 95 ].…”
Section: Biophysical Characterization and Protein Engineering Of Sars...mentioning
confidence: 78%
See 3 more Smart Citations